Analisis determinasi pajak daerah dan hubungan dengan pertumbuhan ekonomi Kabupaten Muaro Jambi - Bustomi Bustomi; Zamzami Zamzami; Selamet Rahmadi (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
The study aims to analyze the factors that influence local tax revenues and the relationship between economic growth and local tax revenues in Muaro Jambi Regency. The data used are secondary data sourced from the Muaro Jambi Regency Central Bureau of Statistics and the Muaro Jambi District Revenue Service. Data analysis used multiple regression models and Pearson correlation. The results of the analysis found: 1) simultaneously and partially, the regional tax revenue of Muaro Jambi Regency was influenced by the number of business units, per capita income and the number of taxpayers; 2) there is a significant positive relationship between economic growth and local tax revenues in Muaro Jambi Regency.